Upregulation of peroxide scavenging enzymes and multidrug efflux proteins highlight an active sodium hypochlorite response in Pseudomonas fluorescens biofilms. Issue 3 (16th March 2019) - Lipus, Daniel; Vikram, Amit; Gulliver, Djuna; Bibby, Kyle
Abstract: The oxidative biocide sodium hypochlorite is among the most commonly used antimicrobial agents in the control of surface-attached microbial communities (biofilms). Clarifying the genetic response of microorganisms in biofilms to hypochlorite may contribute to improved biofilm control strategies. Here, RNA-seq was used to investigate the differential gene expression response of industrially relevant Pseudomonas fluorescens biofilms to sub-lethal concentrations of sodium hypochlorite. Pseudomonas biofilms responded to hypochlorite exposure with increased transcription of genes encoding peroxide scavenging enzymes (e.g., alkyl hydroperoxide reductase (Ahp) and hydroperoxide resistance protein (Ohr)), oxidative stress repair enzymes (e.g., the periplasmic sulfoxide reductase YedYZ complex), and multidrug efflux (e.g., MexEF pumps). In addition, genes involved in amino acid synthesis and energy metabolism were down-regulated following hypochlorite exposure. This work improves the current understanding of genetic response mechanisms to biocides and contributes to the optimization of biocides and application strategies.